Some macromolecular abnormalities developed by interaction of malathion+ cypermethrin in Tribolium castaneum (Herbst) larvae - Saleem, Mushtaq A; Asfaq, Muhammad; Hussain, Riaz; Shakoori, Abdul Rauf (University Journal of Zoology, Rajshahi University, 2007)
Key words: malathion; cypermenthrin; macromolecultes, Tribolium; larvae Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 9-11